Environment-Associated Variations in Blood Metabolism of Mongolian Cattle Grazing in the Alxa Desert of China - Chao Hai; Dongchao Pei; Yuqing Yang; Lishuang Song; Xuefei Liu; Chunling Bai; Guanghua Su; Lei Yang; Guangpeng Li (Veterinary Sciences)
Desert environments pose severe challenges to livestock survival. This study examined climate-driven physiological and metabolic adaptations in 258 Mongolian cattle from six regions of the Alxa Desert, China. Serum biochemical indices were measured and analyzed using linear models to assess the effects of climate, sex, and age. Climate significantly affected key blood parameters, including glucose (p < 0.001), creatinine (p < 0.001), alkaline phosphatase (p < 0.001), and lactate (p = 0.034). Additionally, sex significantly influenced lactate dehydrogenase (p = 0.049), bicarbonate (p = 0.0061), urea (p = 0.0055), and triglycerides (p = 0.039), while age affected total protein (p = 0.020), LDL-C (p = 0.0097), and cholesterol (p < 0.001). Glucose levels were negatively correlated with body size traits. Metabolomic profiling showed that cattle in arid, high-radiation areas exhibited reduced TCA cycle and fatty acid metabolism, with concurrent carbohydrate accumulation, including glucose, fructose, and mannose. Enhanced amino acid metabolism increased proline, valine, tyrosine, and tryptophan levels, potentially supporting physiological stability under heat and drought stress. These findings reveal how Mongolian cattle modulate metabolism in response to desert climates, offering insights into livestock adaptation and informing breeding strategies for resilience in harsh environments.